The availability of the body - Mordacci, Roberto (Medicina e Morale, 1994)
In the present article, which will be published in two parts in different issues of this journal, the author developes an analysis of the moral meaning of biomedical research, in order to sketch out an ethical characterization of the situation of those who participate as volunteers in the experimentation of new drugs, particularly in phase 1 trials. Taking as a starting point the consideration of the nature of biomedica] research, interpreted as the search for a knowledge oriented towards the improvement of the ability to cure the sick, the ethical meaning of the participation of patients or heaJthy volunteers in experimentation is described as "availability" to contribute to the efforts of the researcher to help the suffering ones. Contrary to this attitude is that of "disposition" of the body by those who (subjects or researchers) consider it merely as a means for experimentation or as an instrument for their advantages. The analysis of the results of a short survey between researchers and healthy volunteers concerning the motives of their actions gives some data on the difficulty of translating into reality the perceived values of biomedical research: the prevailing motive for participation in experiments is the economical inducement, while there is scarce interest for the actual relevance of the goals of research. As a consequence, the actual practice of experimentation seems to be inscribed in a widespread attitude of "disposition" of one's own and other's body.